The effect of micro jets on wall pressure for sonic under expanded flow - Ashfaq, Syed; Khan, Sher Afghan (IJERA, 2014)
This paper presents the experimental results on the flow characteristics of a suddenly expanded flow from the convergent nozzle for sonic under expanded case. In the present study micro jets were used to investigate the wall pressure in the enlarged duct. Accordingly an active control in the form of four micro jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region was employed. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied are 2.56, 3.24, 4.84 and 6.25. The length-to-diameter (i.e. L/D) ratio of the sudden expansion duct was varied from 10 to 1. To study the effect of micro jets on the quality of flow in the enlarged duct wall pressure was measured and from the results it is found that the micro jets do not disturb the flow field in the duct. From the results, it is also seen that for L/D in the range L/D = 10 and 8 the flow remains oscillatory mostly for all the area ratios. However, these oscillations are suppressed gradually with the increase in the area ratio, also for all the L/D in the range 3 to 6. The nozzle pressure ratio (NPR) was varied from 1 to 3, however, in the present paper results are presented for under expanded case to ascertain the effectiveness of the micro jets under the influence of favorable pressure gradient (i.e. Pe/Pa = 1.5). The present study explicitly reveals that, the wall pressure in a suddenly expanded axi-symmetric duct can be controlled by employing micro jets.